Energy-saving tecnologies with the use of water treat the magnetic fields - Zhuravska, Nataliya; Malkin, Eduard (КНУБА, 2015)
The current hypotheses of water structure and influence of the magnetic field on the change in its structure have been analyzed. The hypotheses of the feasibility of using highfrequency electromagnetic fields to enhance their impact on the water structure and the stability of this process have been formulated. Experimental studies using water treated in the high-frequency electromagnetic fields for the ecoconcrete production have been carried out.
Keywords: magnetized water; field density; wave motion frequency; water processing time in the field.